2016
DOI: 10.1021/acschembio.6b00222
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Activated HNO Release from a Ruthenium Antiangiogenesis Complex and HIF-1α Inhibition for Cancer Therapy

Abstract: Metallonitrosyl complexes are promising as nitric oxide (NO) donors for the treatment of cardiovascular, endothelial, and pathogenic diseases, as well as cancer. Recently, the reduced form of NO– (protonated as HNO, nitroxyl, azanone, isoelectronic with O2) has also emerged as a candidate for therapeutic applications including treatment of acute heart failure and alcoholism. Here, we show that HNO is a product of the reaction of the RuII complex [Ru(bpy)2(SO3)(NO)]+ (1) with glutathione or N-acetyl-L-cysteine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Among these, thiol species, such as Cys and reduced glutathione (GSH), attract the most attention due to their cellular abundance and potent reactivity. Cys and GSH have been widely used to trigger biologically active molecules and prodrugs to release caged compounds, including sulfur dioxide (SO 2 ), 11 nitroxyl (HNO), 12 and anti-cancer drugs. 13 Importantly, thiol activation strategies have been adopted in H 2 S donor development and several thiol labile H 2 S donors exhibit promising protections in animal models with some of them currently in clinical trials.…”
mentioning
confidence: 99%
“…Among these, thiol species, such as Cys and reduced glutathione (GSH), attract the most attention due to their cellular abundance and potent reactivity. Cys and GSH have been widely used to trigger biologically active molecules and prodrugs to release caged compounds, including sulfur dioxide (SO 2 ), 11 nitroxyl (HNO), 12 and anti-cancer drugs. 13 Importantly, thiol activation strategies have been adopted in H 2 S donor development and several thiol labile H 2 S donors exhibit promising protections in animal models with some of them currently in clinical trials.…”
mentioning
confidence: 99%
“…In vitro studies comparing NO release capacity demonstrated that Complex I is capable of releasing NO after reacting with thiols and presents superior physico-chemical properties and stability compared to other metal complexes ( Silva et al, 2006 , 2011 ). In addition to NO, the thiol reaction with metallonitrosyl complexes, such as Complex I, can generate HNO (nitroxyl) ( Silva Sousa et al, 2016 ). Nitroxyl donors have also analgesic, anti-inflammatory and microbicide actions ( Zarpelon et al, 2013 ; Staurengo-Ferrari et al, 2014b , 2017 ; Longhi-Balbinot et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…evaluated the leishmanicidal potential of the ruthenium nitrosol complex (RuNO, S8) against L. brasiliensis by means of an in vitro (mice dermal fibroblasts) and an in vivo study (using hamsters) [41] . The nitrosyl ruthenium complexes have proven biological activity, such as antiparasitic, antiangiogenic, analgesic, gastroprotective and cerebral neuroprotection [44–49] . In this study, the authors showed that RuNo had no cytotoxic effect on dermal fibroblasts at any of the concentrations tested.…”
Section: New Molecules With Potential For Treatmentmentioning
confidence: 95%